Interrupting Effect of Social Distancing on Ischemic Heart Disease, Asthma, Stroke, and Suicide Attempt Patients by PM2.5 Exposure - Choi, Minseo; Son, Mia; Bae, Sanghyuk; Lee, Whanhee; Kim, Kyung-Nam; Hyun, Jung K (Yonsei medical journal, 2024)
This study aimed to examine the interrupting effect of social distancing (SD) on emergency department (ED) patients with ischemic heart disease (IHD), stroke, asthma, and suicide attempts by PM2.5 exposure in eight Korean megacities from 2017 to 2020.PURPOSEThis study aimed to examine the interrupting effect of social distancing (SD) on emergency department (ED) patients with ischemic heart disease (IHD), stroke, asthma, and suicide attempts by PM2.5 exposure in eight Korean megacities from 2017 to 2020.The study used National Emergency Department Information System and AirKorea data. A total of 469014 patients visited EDs from 2017 to 2020. Interrupted time series analysis was employed to examine changes in the level and slope of the time series, relative risk, and confidence intervals (CIs) by PM2.5 exposure. The SD level was added to the sensitivity analysis.MATERIALS AND METHODSThe study used National Emergency Department Information System and AirKorea data. A total of 469014 patients visited EDs from 2017 to 2020. Interrupted time series analysis was employed to examine changes in the level and slope of the time series, relative risk, and confidence intervals (CIs) by PM2.5 exposure. The SD level was added to the sensitivity analysis.The interrupted time series analysis demonstrated a significant increase in the ratio of relative risk (RRR) of IHD patients in Seoul (RRR=1.004, 95% CI: 1.001, 1.006) and Busan (RRR=1.007, 95% CI: 1.002, 1.012) post-SD. Regarding stroke, only patients in Seoul exhibited a significant decrease post-SD (RRR=0.995, 95% CI: 0.991, 0.999). No significant changes were observed for asthma in any of the cities. In the case of suicide attempts, Ulsan demonstrated substantial pre-SD (RR=0.827, 95% CI: 0.732, 0.935) and post-SD (RRR=1.200, 95% CI: 1.057, 1.362) differences.RESULTSThe interrupted time series analysis demonstrated a significant increase in the ratio of relative risk (RRR) of IHD patients in Seoul (RRR=1.004, 95% CI: 1.001, 1.006) and Busan (RRR=1.007, 95% CI: 1.002, 1.012) post-SD. Regarding stroke, only patients in Seoul exhibited a significant decrease post-SD (RRR=0.995, 95% CI: 0.991, 0.999). No significant changes were observed for asthma in any of the cities. In the case of suicide attempts, Ulsan demonstrated substantial pre-SD (RR=0.827, 95% CI: 0.732, 0.935) and post-SD (RRR=1.200, 95% CI: 1.057, 1.362) differences.While the interrupting effect of SD was not as pronounced as anticipated, this study did validate the effectiveness of SD in modifying health behaviors and minimizing avoidable visits to EDs in addition to curtailing the occurrence of infectious diseases.CONCLUSIONWhile the interrupting effect of SD was not as pronounced as anticipated, this study did validate the effectiveness of SD in modifying health behaviors and minimizing avoidable visits to EDs in addition to curtailing the occurrence of infectious diseases.